C–H Alkylation of Heteroarenes with Alkyl Oxalates by Molecular Photoelectrocatalysis - Xu, Fan; Lai, Xiao-Li; Xu, Hai-Chao (Synlett, 2020)
An oxidant- and metal-free photoelectrocatalytic C–H alkylation reaction of heteroarenes with alkyl oxalates has been developed. Several classes of heteroaromatics, such as quinolines, isoquinolines, pyridines, and phenanthridines, can be alkylated with tertiary or secondary alkyl oxalates. The photoelectrochemical synthesis employs 2,4,5,6-tetra-9H-carbazol-9-ylisophthalonitrile as a molecular catalyst and allows the oxidative transformations to proceed through evolution of hydrogen without a sacrificial chemical oxidant.
Keywords: photoelectrochemistry; photoelectrocatalysis; C–H functionalization; alkyl oxalates; heterocycles